Evaluation of Cinnamomum verum Bark Essential Oil as a Natural Antifungal Agent Against Dermatophytes - Leka Lutpiatina; Annisa Aulia Damayanti; Akhmad Rhafianor; Neni Oktiyani; Aima Insana (Baiman Bauntung Batuah Center, 2026)
Dermatophytosis is a superficial fungal infection that remains a public health problem, particularly in tropical regions, with Trichophyton rubrum and Trichophyton mentagrophytes as the primary causes. Increasing limitations in the use of synthetic antifungals have encouraged the development of natural products as alternative therapies, including Cinnamomum verum stem bark essential oil. This study aimed to analyse the antifungal activity of C. verum stem bark essential oil against T. rubrum and T. mentagrophytes using the disc diffusion method. The study used a true experimental design with a posttest-only control group design. The essential oil was obtained through steam-water distillation with a yield of 0.25% (v/w). Tests against T. rubrum used concentrations of 1%, 2%, 5%, and 10%, while tests against T. mentagrophytes used concentrations of 5%, 10%, 15%, and 20%. Ketoconazole 2% was used as a positive control and dimethyl sulfoxide as a negative control. The inhibition zone diameter was measured after incubation and analysed using One-Way ANOVA and Post Hoc tests. The results showed that the essential oil inhibited the growth of both fungal species at all concentrations tested. The inhibition zone diameter against T. rubrum increased from 21.7 mm to 54.1 mm, while against T. mentagrophytes it increased from 33.6 mm to 48.2 mm. Statistical analysis showed a significant difference between the concentrations of both species (p<0.001). It was concluded that C. verum bark essential oil exhibited in vitro antifungal activity against both T. rubrum and T. mentagrophytes, with the inhibitory activity generally increasing with increasing concentrations. These findings demonstrate the potential of C. verum essential oil as a candidate for a natural antifungal agent based on local resources. Therefore, further research on the characterisation of active compounds, determination of MIC/MFC values, development of topical formulations, and in vivo testing and clinical trials are needed to support its use in dermatophytosis therapy.